FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN IBU HAMIL DALAM MELALUKAN KUNJUNGAN K4 DI PUSKESMAS KASSI- KASSI MAKASSAR - Nurhikmah Nurhikmah (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
The purpose of the study: to find out the factors related to the compliance of pregnant women in conducting a K4 visit at Kassi - Kassi Makassar Health Center. Method: The research design used is a cross sectional study method is a type of research that emphasizes the time of measurement / observation of independent and dependent variable data. The population was all third trimester primigravida and multigravida pregnant women at Kassi - Kassi Makassard Public Health Center using purposive sampling and sample techniques of 68 Trimester III pregnant women. The population in this study were all mothers who received a sample of 61 people with purposive sampling sampling. Results: The results of the study found that the largest proportion of attitudinal factors were positive attitudes as many as 47 people (69.1%) and negative attitudes as many as 21 people (30.9%), while in the gravida factor, pregnant women were 22 people (32.4%) and multigravida as many as 46 people (67.6%). And work factors, not working as many as 42 people (61.8%) and working as many as 26 people (38.2%), while the factor of family support is pregnant women who get good family support as many as 40 people (58.8%) while 28 people don't get support from the family (41.2%). Discussion: Compliance is behavior according to rules and discipline. The purpose of this study was to determine the factors related to adherence of pregnant women to visit K4 at the Kassi - Kassi Makassar Health Center. Conclusion: the conclusion of this study is that there is a relationship between attitude and adherence to K4 visits, there is a gravida relationship with compliance with K4 visits, there is a work relationship with compliance with K4 visits and there is a family support relationship with compliance with K4 visits. Suggestion: It is recommended to health workers, especially midwives, to further increase supervision of the coverage of services for pregnant women, especially coverage of K4 visits